Faktor-Faktor yang Berhubungan dengan Penggunaan KB IUD Pasca Persalinan di Klinik Bidan Lamria Silitonga Amd.Keb Kalimantan Barat - Lufthi Amallkarina; Maryati Sutarno (Universitas Malahayati Lampung, 2025)
ABSTRACT KBPP coverage is still very low. Of the 79 mothers giving birth, only 21 people (26.5%) will use the KBPP IUD in 2023 and in 2024, of the 59 mothers giving birth, only 13 people (22%) will use the KBPP IUD, this is This means that the use of KBPP among mothers giving birth is still very low. to study the factors associated with the use of IUD contraception after childbirth at the Midwife Clinic Lamria Silitonga Amd. Keb West Kalimantan in 2024. Analytical Survey, with a cross sectional approach, the population in this study were all postpartum mothers at the Lamria Silitonga Midwife Clinic Amd. Keb West Kalimantan from January to September 2024 as many as 59 people, with a total sampling technique with a sample size of 59 respondents , using data namely secondary data with checklist sheets, univariate and bivariate analysis using chi square. From the results of the Chi Square test, there is a significant relationship between age and the use of IUD contraception after childbirth (ρ value = 0.000), and the OR value = 0.020, meaning that postpartum mothers aged 20 years or 35 years are more at risk of not using an IUD and vice versa. There is no relationship between parity (ρ value = 0.533) and employment (ρ value = 0.208) with the use of IUD contraception after childbirth at the Midwife Clinic Lamria Silitonga Amd. Keb West Kalimantan in 2024. There is a relationship between age and the use of IUD contraception after childbirth so that this research can be used as a reference in providing postpartum contraception based on the mother's age, whether it is risky or not. Keywords: Age, Parity, Employment, Use of KBPP ABSTRAK Cakupan KBPP masih sangat rendah dari 79 ibu bersalin hanya 21 orang (26,5%) yang menggunakan KBPP IUD pada tahun 2023 dan pada tahun 2024 dari 59 ibu bersalin hanya 13 orang (22%) yang menggunakan KBPP IUD, hal ini berarti penggunaan KBPP pada ibu bersalin masih sangat rendah. Untuk mempelajari Faktor-faktor yang berhubungan dengan penggunaan KB IUD pasca persalinan di Klinik Bidan Lamria Silitonga Amd.Keb Kalimantan Barat Tahun 2024. Survei Analitik, dengan pendekatan secara cross sectional, populasi dalam penelitian ini seluruh ibu pasca persalinan di Klinik Bidan Lamria Silitonga Amd.Keb Kalimantan Barat dari bulan Januari s/d September 2024 sebanyak 59 orang, dengan teknik total samplling dengan jumlah sample 59 responden, memakai data yaitu data sekunder dengan lembar cheklist, analisis univariat dan bivariat menggunakan chi square. Dari hasil uji uji Chi Square yaitu Ada hubungan yang sigifikan antara usia dengan penggunaan KB IUD pasca persalinan (ρ value = 0,000), dan nilai OR=0.020 artinya ibu pasca persalinan yang berusia 20 tahun atau 35 tahun lebih berisiko tidak menggunakan IUD dan begitu pula sebaliknya. Tidak ada hubungan paritas (ρ value = 0, 533) dan pekerjaan (ρ value = 0,208) dengan penggunaan KB IUD pasca persalinan di Klinik Bidan Lamria Silitonga Amd.Keb Kalimantan Barat Tahun 2024. Hubungan usia dengan penggunaan KB IUD pasca persalinan sehingga dengan adanya penelitian ini dapat dijadikan acuan dalam memberikan kontrasepsi pasca salin dilihat dari usia ibu apakah berisiko dan tidak berisiko. Kata Kunci: Usia, Paritas, Pekerjaan, Penggunaan KBPP